Metallic impurity sources behavior during ICRH in EAST. (December 2018) - Urbanczyk, G.; Zhang, X.J.; Colas, L.; Ekedahl, A.; Heuraux, S.; Li, J.G.; Qin, C.M.; Zhao, Y.P.; Zhang, L.; Yang, X.D.
Highlights: High-Z impurity sources during ICRF in EAST were qualitatively localized using EUV spectroscopy. Regions close and magnetically connected to active ICRF antennas are more sensitive to ICRF settings than remote regions whereas divertor region is more sensitive to total power injected. Abstract: High-Z impurities production is often observed during Ion Cyclotron Range of Frequencies (ICRF) waves' injection, which are likely due to RF sheath formation on solid materials. Based on Extreme UV (EUV) spectrometry data, this study in EAST consists in extracting information on plasma-surface interactions during ICRH. Intensities of the different spectral lines normalized to line-integrated plasma density, exhibit different parametric dependencies over scans of ICRH and LH power and for different toroidal phasing between straps. Materials close and magnetically-connected to an active antenna tend to show better correlation with ICRF parameters – such as power and feeding scheme – than those which are far away or not connected. ICRF phasing did not have influence on impurity, probably due to the absence of feedback control. It is further shown that the plasma content in impurities from divertor region better correlates with the total injected power rather than with ICRF power.